Динамічна модель лінійного генератора з постійними магнітами для перетворення енергії хвиль - Кондратенко, І.П.; Ращепкін, А.П.; Ващишин, Д.Д. (Технічна електродинаміка, 2012)
The method of calculating the electrical characteristics of the linear generator was devised, which is part of a device for converting energy of sea waves, considering dynamic modes of inductor motion and reaction of electromagnetic system. The method is based on a compatible solution of the equations of dynamic equilibrium mechanical system (d'Alembert) and electric circuit of three-phase linear generator (equation of the second Kirchhoff law). The design of a linear generator with a inductor realized in the form of a periodic system of permanent magnets. The dependence the linear generator energy characterizes on the nature of the moving inductor at a given wave shape, and examined the impact strength of electromagnetic interaction on the power generated by the generator at the specified parameters of inductor-buoy.